PENGARUH EXPERIENTIAL MARKETING, KUALITAS PELAYANAN, DAN NILAI PELANGGAN TERHADAP KEPUASAN KONSUMEN (Survei Pada Pelanggan Goodboy Barbershop Ponorogo) - Catur Prasetyawan (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to determine the effect of experiential marketing, service quality, and customer value on customer satisfaction at GoodBoy Barbershop Ponorogo customers. The sample in this study were 110 respondents. The testing stages used include instrument testing, classical assumption test, coefficient of determination test and hypothesis testing. The analysis used in this study is multiple linear regression analysis. The results of this study indicate that: (1) Experiential marketing has a positive and significant effect on consumer satisfaction. (2) Service quality has a positive and significant effect on customer satisfaction. (3) Customer value has a positive and significant effect on customer satisfaction. (4) Experiential marketing, service quality, and customer value simultaneously have a positive and significant effect on customer satisfaction.